Definition and risk factors for early recurrence in patients with laryngeal cancer after initial surgery - Qin Lin; Longxiang Zheng; Xiaoqiang Chen; Desheng Wang (Scientific Reports)
Abstract To determine an optimal cut-off value for distinguishing early and late recurrence in patients with laryngeal cancer after initial surgery and to evaluate the risk factors for early recurrence. This retrospective study included 328 patients with laryngeal cancer who underwent initial resection in our hospital from January 2014 to April 2018. A minimum P-value approach was used to determine the optimal cut-off value to divide patients into early and late recurrence groups. The clinicopathological characteristics were compared between the two groups. The risk factors for early recurrence were evaluated using logistic regression analysis. The optimal cut-off value to identify between early recurrence (n = 51, 50.5%) and late recurrence (n = 50, 49.5%) was 17 months (p < 1e−17). The overall survival of the late recurrence group (48.36 ± 16.02 months) was longer than the early recurrence group (32.61 ± 19.65 months) significantly (p < 0.001). Lymphovascular invasion (p = 0.038), patients without adjuvant radiotherapy (p = 0.043), advanced tumor, node, metastasis (TNM) stage (p = 0.035), and positive surgical margins (p = 0.045) were independent risk factors for early recurrence. The best cut-off value to identify early recurrence after initial surgery for laryngeal cancer was 17 months. Intensive follow-up and adjuvant radiotherapy may be beneficial for patients with risk factors for early recurrence.